Undesirable conclusions in the sciences: a pluralistic perspective (Culturas Científicas, 2023)
The present work seeks to address, within the context of the debate around the influence of extra-epistemic values in the sciences, the problem regarding certain scientific investigations that could contain undesirable conclusions, in the sense that their content could affect certain social groups. Following the reasoning of the pluralist philosopher Philip Kitcher, the discussion is situated around the renunciation of the search for certain truths, when these may conflict with certain moral, political or social values that we are not willing to transgress. In this line, emphasis is placed on the influence of moral considerations that can influence our judgment about the truths that describe the world, as well as on the moral dimension of human action that turns out to be an inalienable aspect, which is entirely applicable to scientific activity.
Keywords: extra epistemic values, scientific pluralism, undesirable conclusions; extra epistemic values; scientific pluralism; undesirable conclusions